PUBLIC FINANCE IN THE CONDITIONS OF WAR: CHALLENGES OF UNCERTAINTY AND PATHS OF ADAPTATION - Bei, Snizhana; Doliuk, Alla (Social Economics, 2025)
The purpose of this article is to study the peculiarities of the functioning of Ukraine's public finance system under martial law, identify key challenges associated with high levels of economic and social uncertainty, and justify possible ways of adapting budgetary and financial policy to ensure the sustainability, balance, and efficiency of public resource management. The article analyzes the current state of public finances in Ukraine under martial law, describes the main trends in the formation of revenues and expenditures of the state budget, the impact of military actions on the tax system, interbudgetary relations, and financial decentralization. It identifies the main challenges facing the state's financial system, including a sharp increase in military and social spending, a reduction in budget revenues due to a decline in economic activity, a growing budget deficit, and the need for external financing. Particular attention is paid to the role of international financial assistance in maintaining macroeconomic stability, ensuring the solvency of the state, and financing critically important sectors of the economy. The problems of effective public finance management during wartime are highlighted, in particular the issues of transparency of budgetary processes, targeted use of funds, risks of corruption, and restrictions in the area of financial control. Directions for improving public finance management mechanisms in conditions of uncertainty are substantiated, including the digitization of financial processes, strengthening anti-crisis planning, optimizing budget expenditures, improving the effectiveness of financial control, and developing strategic forecasting. Recommendations are proposed to improve the country's financial stability in the medium and long term, which include aligning domestic financial capabilities with external support, improving the efficiency of budget resource use, developing effective public debt management mechanisms, and enhancing financial security as a component of national stability.